1964
DOI: 10.1136/hrt.26.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Blalock-Taussig Anastomosis for Tetralogy of Fallot: A Ten-to-Fifteen Year Follow-Up

Abstract: The mortality rate for total correction of Fallot's tetralogy on cardiac bypass with or without a Blalock-Taussig anastomosis is still relatively high (Kirklin et al., 1959;Lillehei et al., 1957; Taussig et al., 1962). Favourable reports concerning the results of the Blalock-Taussig procedure in patients followed for five to ten years have been published (Taussig and Bauersfeld, 1953;Campbell and Deuchar, 1953;White et al., 1956;Rumel, 1958;Brock, 1959;Shumacker and Mandelbaum, 1960). While total correction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Compared with the untreated patients, the results of the B-T shunts in 30 patients with tetralogy of Fallot between 1948 and 1952 showed that 67% of the patients survived with clinical improvement and were leading a relatively normal life. 42 Subsequently, the B-T shunts obtained a permanent improvement during a 10-to 15-year follow-up. 43,44 However, the effectiveness of the 4-mm-diameter conduit was doubted due to the occurrence of conduit failure at one year after implantation, while other sized conduits remained widely patent.…”
Section: Prognosismentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with the untreated patients, the results of the B-T shunts in 30 patients with tetralogy of Fallot between 1948 and 1952 showed that 67% of the patients survived with clinical improvement and were leading a relatively normal life. 42 Subsequently, the B-T shunts obtained a permanent improvement during a 10-to 15-year follow-up. 43,44 However, the effectiveness of the 4-mm-diameter conduit was doubted due to the occurrence of conduit failure at one year after implantation, while other sized conduits remained widely patent.…”
Section: Prognosismentioning
confidence: 93%
“…Compared with the untreated patients, the results of the B‐T shunts in 30 patients with tetralogy of Fallot between 1948 and 1952 showed that 67% of the patients survived with clinical improvement and were leading a relatively normal life 42 . Subsequently, the B‐T shunts obtained a permanent improvement during a 10‐ to 15‐year follow‐up 43,44 …”
Section: Prognosismentioning
confidence: 99%
“…20 Abnormalities in blood flow, arm length and grip strength have also been demonstrated in ipsilateral arm of patients with Blalock Taussig shunts. 21,24 However, these results have not been uniformly demonstrated, with Shenberger et al 7 finding no difference in blood flow nor static forearm strength, 9 years after subclavian flap repair.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, disturbances in the blood supply and develop ment of the arm on the side of the anastomosis have been reported in follow-up studies [3,5], However, there is no evidence in the literature for abnormalities of muscle blood supply in the operated extremity.…”
mentioning
confidence: 99%